Magma Chamber Associated to Deep Faults in Copahue Active Volcanic Complex, South America, Suggested by Magnetotelluric Study - Borzotta, E.; Caselli, A.T.; Mamani, M.J. (Геофизический журнал, 2018)
Magnetotelluric studies were carried out in 1993 and 2008 inside the caldera of Copahue Volcanic Complex, located in South America, at the border between Chile and Argentina (37°45' S; 71°10.2' W). The main effusive centre of this complex is the Copahue Active Volcano, which constitutes an important geothermal zone. The study of the crust and the investigation of possible magma chambers were the objectives of this survey.